Chromosome-scale genome assembly of Prunus pusilliflora provides novel insights into genome evolution, disease resistance, and dormancy release in Cerasus L. Issue 1 (10th April 2023) - Jiu, Songtao; Chen, Baozheng; Dong, Xiao; Lv, Zhengxin; Wang, Yuxuan; Yin, Chunjin; Xu, Yan; Zhang, Sen; Zhu, Jijun; Wang, Jiyuan; Liu, Xunju; Sun, Wanxia; et al.
Abstract: Prunus pusilliflora is a wild cherry germplasm resource distributed mainly in Southwest China. Despite its ornamental and economic value, a high-quality assembled P. pusilliflora genome is unavailable, hindering our understanding of its genetic background, population diversity, and evolutionary processes. Here, we de novo assembled a chromosome-scale P. pusilliflora genome using Oxford Nanopore, Illumina, and chromosome conformation capture sequencing. The assembled genome size was 309.62 Mb, with 76 scaffolds anchored to eight pseudochromosomes. We predicted 33, 035 protein-coding genes, functionally annotated 98.27% of them, and identified repetitive sequences covering 49.08% of the genome. We found that P. pusilliflora is closely related to P. serrulata and P. yedoensis, having diverged from them 41.8 million years ago. A comparative genomic analysis revealed that P. pusilliflora has 643 expanded and 1, 128 contracted gene families. Furthermore, we found that P. pusilliflora is more resistant to C. viniferum, P. capsici, and Pst DC3000 infections than cultivated P. avium . P. pusilliflora also has considerably more nucleotide-binding site-type resistance gene analogs than P. avium, which explains its stronger disease resistance. The respective cytochrome P450 and WRKY families of 263 and 61 proteins were divided into 42 and eight subfamilies in P. pusilliflora, respectively. Furthermore, 81 MADS-box genes were identified in P. pusilliflora, accompanying expansions of the SVP and AGL15 subfamilies and loss of the TM3 subfamily. Our assembly of a high-quality P. pusilliflora genome will be valuable for further research on cherries and molecular breeding.